Importance of Management for Achieving Goals of Business - Lubis, Yusniar; Thanh Nguyen, Phong; V. Zelinskaya, Maria; Shankar, K.; S. Ciptaningsih, Eka Maya (Opción, 2019)
Managing any business is one of the important human activities. In cur- rent time every individuals start making social organizations to com- plete their aims in life. These aim must complete by managing people on work, so managing has been essential to substantiate the coordination of individual efforts. Economically the work load is increase for man- agers and lots of organization have larger groups, so they must have to allocate specific task for employee and manages to manage work. Hence for, social control information has become crucial inside the ways in which managers manage advanced organizations. It is a method or se- ries of continuous and connected activities. In this paper a study of im- portance of management for achieving goals of business is review and explain for economic business. These paper deal with the management of business by manager in any small or big organization. These s neces- sary to build a proper successful business.